Discharge in high pressure gas initiated by fast electron beam; Proceedings of the Xth International Conference on Phenomena in Ionized Gases, Oxford, september 13-18, 1971; Pt. 1 - Kovalchuk B. M.; Kremnev V. V.; Mesyats G. A. Gennady Andreyevich; Potalitsyn Yu. F. (1971, 1971)
В фонде НТБ ТПУ отсутствует